English Reading Comprehension of Students at International Theravada Buddhist Missionary University - rita, suca (วารสารพุทธอาเซียนศึกษา, 2024)
The study is titled “English reading comprehension of students at International Theravada Buddhist Missionary University”. The objectives of this research were 1) to study the difficulties of English reading comprehension of students at International Theravada Buddhist Missionary University, Yangon, Myanmar, 2) to find out how to solve students' English reading comprehension problems at International Theravada Buddhist Missionary University, Yangon, Myanmar. The research used both quantitative and qualitative methods. The study collected data from 60 second-year students through questionnaires and conducted in-depth interviews with five teachers to gather their opinions and suggestions. The findings indicated that the highlights critical issues affecting students' reading comprehension are primarily linked to a lack of interest, poor reading habits, and limited vocabulary and grammar knowledge. Many students rely on teachers or peers for answers instead of engaging with the material themselves. Additionally, students lack effective reading strategies and techniques, which are essential for understanding texts. Observations revealed that teachers often focus more on grammar than on teaching reading skills, with some displaying a lack of enthusiasm and competence in teaching reading. Overall, both student-related factors and deficiencies in teaching practices significantly contribute to challenges in reading comprehension. The suggestion to further research the study recommends was the importance of investigating various English language skills among university students, specifically focusing on writing, speaking, and listening abilities. It highlights the need to explore and improve students' vocabulary to enhance their communication clarity and effectiveness. Additionally, it underscores the significance of phonics as a foundational element in English learning, aiding students in the correct pronunciation and writing of words.